2016
DOI: 10.1095/biolreprod.116.142174
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Synthesis and Transport at the Uterine-Placental Interface of Pigs: Cell-Specific Localization of SLC2A5, SLC2A8, and Components of the Polyol Pathway

Abstract: The fetal fluids and uterine flushings of pigs contain higher concentrations of fructose than glucose, but fructose is not detected in maternal blood. Fructose can be synthesized from glucose via enzymes of the polyol pathway, aldose reductase (AKR1B1) and sorbitol dehydrogenase (SORD), transported across cell membranes by solute carriers SLC2A5 and SLC2A8, and converted to fructose-1-phosphate by ketohexokinase (KHK). SLC2A8, SLC2A5, AKR1B1, SORD, and KHK mRNAs and proteins were analyzed using quantitative PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…In the placenta, the same pathway is responsible for the higher fructose concentration in the umbilical cord than in maternal blood. This has been observed mainly in ungulates (Steinhauser et al, 2016), but placental fructose synthesis has been well documented in humans too (Maragoudakis et al, 1984;Trindade et al, 2011). The functional significance of this observation remains unknown, although some authors propose that fructose may act as a growth factor during normal fetal development (Bazer et al, 2012;Wang et al, 2016).…”
Section: Endogenous Fructose Productionmentioning
confidence: 98%
“…In the placenta, the same pathway is responsible for the higher fructose concentration in the umbilical cord than in maternal blood. This has been observed mainly in ungulates (Steinhauser et al, 2016), but placental fructose synthesis has been well documented in humans too (Maragoudakis et al, 1984;Trindade et al, 2011). The functional significance of this observation remains unknown, although some authors propose that fructose may act as a growth factor during normal fetal development (Bazer et al, 2012;Wang et al, 2016).…”
Section: Endogenous Fructose Productionmentioning
confidence: 98%
“…Aldose reductase B1 (AKR1B1 or ALR2), a NADPH-dependent enzyme that belongs to the aldo-keto reductase protein superfamily (Bohren et al, 1989;Hyndman et al, 2003), has been reported to play an essential role in both male and female reproductive systems in humans (Bresson et al, 2011), cattle (Frenette et al, 2004;Girouard et al, 2009), rats (Kobayashi et al, 2002), sheep (Yang et al, 2019), and pigs (Steinhauser et al, 2016;Pérez-Patiño et al, 2018). This enzyme is known to be involved in the polyol pathway for fructose production, specifically in the conversion of glucose into sorbitol (Kobayashi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The porcine placenta lacks phosphate‐activated glutaminase. The enzymes catalyzing the indicated reactions are as follows: (1) enzymes for the degradation of amino acids in maternal tissues; (2) asparagine synthetase; (3) enzymes for the synthesis of purines and pyrimidines; (4) NADPH‐dependent aldose reductase and NAD + ‐dependent sorbitol dehydrogenase (Steinhauser et al, ); and (5) ATP‐dependent fructose kinase. KGM, α‐ketoglutaramate; OAA, oxaloacetate…”
Section: Role Of the Placenta In Amino Acid Metabolismmentioning
confidence: 99%